Kazakhstan Economic Update No. 1, Spring 2015 : Low Oil Prices--An Opportunity to Reform - World Bank (Washington, DC, 2015)
Kazakhstan’s gross domestic product (GDP) growth slowed in 2014 because of weak demand and the fall in oil prices. Government policies were directed to mitigating the impact of lower oil prices on growth. So far labor market and poverty reduction outcomes do not seem to have been affected by the downturn, thanks to continued job creation, inter-sectoral and geographic mobility, and new employer social arrangements. The same factors that slowed growth in 2014 are also clouding the outlook for the medium term. Trade and transport services will be affected by a knock-on effect from lower mining and industrial exports. However, GDP growth is projected to recover gradually along with oil prices. Continuing the current policy mix of modest fiscal expansion and tight monetary policy will not boost the economy; for the medium term a more neutral monetary policy stance and a more flexible exchange rate regime will more sustainably support growth.